Parental smoking and child poverty in the UK: an analysis of national survey data - Belvin, Charmaine; Britton, John; Holmes, John; Langley, Tessa (BioMed Central, 2015)
BACKGROUND: In 2011/12 approximately 2.3 million children, 17% of children in the UK, were estimated to be in relative poverty. Cigarette smoking is expensive and places an additional burden on household budgets, and is strongly associated with socioeconomic deprivation. The aim of this study was to provide an illustrative first estimate of the extent to which parental smoking exacerbates child poverty in the UK.